ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA USAHA PRODUK MAKANAN PASTEL - Cyntiara Teresa Salsabila; Dian Sudiantini, Lulu Ilmaknun Al Zahra, Olga Gabriellina Shinta Dewi, Silvia Ashjda Yuzran (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Job satisfaction with employee performance is very much needed. company, because employees are very important assets, employees will automatically not be able to concentrate fully in carrying out their work if employees work in uncomfortable conditions and do not appreciate their potential. Employee job satisfaction is important to build enthusiasm for work and foster increased employee performance. In this research, employee job satisfaction can be influenced by employee work performance and leadership, work performance is the result of work that an employee achieves in carrying out work in accordance with the responsibilities given, while leadership is a process that can influence other people to understand and Jul agrees on what and how to do it. The aim of this research is to analyze the influence of job satisfaction on employee performance in the pastel food product business. The research method used in this research is a qualitative method. Qualitative analysis is carried out by analyzing Internet Searching or online searches. From the research results it was found that there was a positive influence on job satisfaction consisting of indicators, work quantity, quality. work, creativity, responsibility, and personal qualities. Increasing job satisfaction with employee performance can still be further improved in order to improve employee performance.